Adjunctive use of controlled‐release pregabalin in adults with treatment‐resistant partial seizures: A double‐blind, randomized, placebo‐controlled trial. Issue 8 (24th June 2014) - French, Jacqueline; Brandt, Christian; Friedman, Daniel; Biton, Victor; Knapp, Lloyd; Pitman, Verne; Chew, Marci; Dubrava, Sarah; Posner, Holly B.
Summary Objectives To assess the efficacy and tolerability of add‐on pregabalin controlled‐release formulation (PGB‐CR) (doses of 165 or 330 mg/day) in patients with partial‐onset seizures (POS). Methods This was a randomized, double‐blind (DB), parallel‐group study of PGB‐CR once‐daily as adjunctive treatment in adults with treatment‐resistant partial seizures. After an 8‐week baseline period, eligible patients were randomized (1:1:1) to placebo, PGB‐CR 165 mg, or PGB‐CR 330 mg for 14 weeks, including a 2‐week dose escalation. Primary endpoint was the loge‐transformed 28‐day seizure rate for all POS with observable component during the full 14‐week double‐blind treatment phase. Secondary endpoints included the 50% responder rate and percent change from baseline in 28‐day POS rate. Results Three hundred twenty‐three patients were randomized and received treatment; placebo (n = 110), PGB‐CR 330 mg (n = 100), PGB‐CR 165 mg (n = 113); and 287 (88.9%) completed the trial. The primary efficacy analysis result, expressed as percent reduction from placebo, was 13.1% and 1.0% for PGB‐CR 330 mg and PGB‐CR 165 mg, respectively, and was not statistically significant (p = 0.091, 0.908). The proportion of 50% responders was similar for placebo (35.8%) and 165 mg PGB‐CR (37.8%) and nominally higher for 330 mg PGB‐CR (45.9%, p = 0.125 compared to placebo). The LS mean estimates of the percent change from baseline for placebo (−5.7%) was nominally smaller than 165 mg PGB‐CR (−15.0%, p = 0.540) and 330 mg PGB‐CR (−31.5%, p = 0.079); however, the median percent changes from baseline were not as well differentiated (placebo, −35.4%; 165 mg PGB‐CR, −38.0%; 330 mg PGB‐CR −43.4%). Rates of adverse events (AEs) were low for placebo and study drug; the most frequent reported AEs were dizziness, somnolence, and fatigue, consistent with the immediate‐release formulation. Significance Results from this trial did not demonstrate that PGB‐CR is effective in reducing seizure frequency below that of placebo. Both doses of PGB‐CR were shown to be safe and well‐tolerated. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.